Efeito do nado sustentado sobre o metabolismo intermediário e antioxidante de matrinxã (Brycon amazonicus) - Fabrizzi, Fernando (2015)
The significant increase in fish consumption in recent decades has led to considerable extractive exploitation that can bring harmful consequences to the environment and the community living the fishing sustainable exploitation. Therefore, it is essential the search for ways to mitigate this condition. The fish farming development appears as an alternative capable of contribute to the solution of this problem, since it would be possible to maintain the social demand for fish. In a strategic way, the exercise have been standing out by the effects produced directly on animal physiology. On fish, there is sustained evidence that swimming practices brings improvements in hematological parameters, in the metabolic profile of the animals and that may lead them to have great benefits into health and well-being. In study was evaluated the hematological and metabolic parameters and antioxidant response of Brycon amazonicus under control or not of sustained swimming and submitted or not to nitrite excess stress. Currently a major problem in recirculation systems face in fish farming in their biological filters.The submitted animals to sustained swimming activity had an attenuation indicative metabolic adjustment on the stress caused by nitrite. The animals on sustained swimming effects optimizes the carbohydrates oxidation aiming the energy production, thereby minimizing amino acids oxidation for this purpose. Similarly, the fish that were submitted to sustained swimming had produced reduced FOX values, indicating that this swimming activity can be a great tool against oxidative stress. In conclusion, Matrinxãs adapted to sustained swimming have a better ability to face oxidative stress caused by environmental nitrite, making changes hematological, biochemical and metabolism, which can improve oxidative metabolic processes.